The Great Delusion : Liberal Dreams and International Realities - Mearsheimer, John J. (London Yale University Press, 2018)
"It is widely believed in the West that the United States should spread liberal democracy across the world, foster an open international economy, and build international institutions. The policy of remaking the world in America$1 (Bs image is supposed to protect human rights, promote peace, and make the world safe for democracy. But this is not what has happened. Instead, the United States has become a highly militarized state fighting wars that undermine peace, harm human rights, and threaten liberal values at home. In this major statement, the renowned international-relations scholar John Mearsheimer argues that liberal hegemony--the foreign policy pursued by the United States since the Cold War ended--is doomed to fail. It makes far more sense, he maintains, for Washington to adopt a more restrained foreign policy based on a sound understanding of how nationalism and realism constrain great powers abroad. The Great Delusion is a lucid and compelling work of the first importance for scholars, policymakers, and everyone interested in the future of American foreign policy"-Publisher's website.s
Keywords: United States -- Foreign relations -- 21st century -- United States -- Foreign relations -- 1989